Tinjauan Hukum Islam dan UU No 13 Tahun 2003 tentang Ketenagakerjaan terhadap Hak Upah Tenaga Honorer - Afrah Nur Athifah; Encep Abdul Rojak; Akhmad Yusup (Bandung Conference Series: Sharia Economic Law, 2023)
Abstract. According to Hanafiyah scholars, wages/ujrah are transactions for a benefit with certain permissible rewards. So, wages are a form of compensation for services that have been provided by workers. Wages according to Law No. 13 of 2003 concerning Manpower concerning the definition of wages in Article 1 paragraph 30 which reads: "Wages are rights of workers/laborers received and expressed in the form of money as a reward from employers or employers to workers/laborers which are determined and paid according to a work agreement, agreement, or laws and regulations, including benefits for workers/laborers and their families for work and/or services that have been or will be performed". This study aims to find answers to the main issues, namely how to review Islamic law and Law no. 3 of 2003 concerning Employment for LPP RRI Belitung honorary wage rights in East Belitung Regency. In this study using qualitative research methods with data collection techniques by way of interviews, and documentation with qualitative descriptive methods. The result of this study is the provision of wages that are not in accordance with the system of wage rights according to Islamic law and the applicable UMR/UMP. Abstrak. Menurut ulama Hanafiyah upah/ ujrah adalah transaksi terhadap suatu manfaat dengan imbalan tertentu yang dibolehkan. Jadi, upah adalah bentuk kompensansi atas jasa yang telah diberikan oleh tenaga kerja. Upah menurut UU No.13 tahun 2003 tentang Ketenagakerjaan mengenai pengertian upah dalam pasal 1 ayat 30 yang berbunyi : “Upah adalah hak pekerja/buruh yang diterima dan dinyatakan dalam bentuk uang sebagai imbalan dari pengusaha atau pemberi kerja kepada pekerja/buruh yang ditetapkan dan dibayarkan menurut suatu perjanjian kerja, kesepakatan, atau peraturan perundang-undangan, termasuk tunjangan bagi pekerja/buruh dan keluarganya atas suatu pekerjaan dan/atau jasa yang telah atau akan dilakukan”. Penelitian ini bertujuan untuk mencari jawaban dari pokok permasalahan, yaitu bagaimana tinjauan hukum Islam dan UU No. 3 tahun 2003 tentang Ketenagakerjaan terhadap hak upah tenaga honorer LPP RRI Belitung di Kabupaten Belitung Timur. Dalam penelitian ini menggunakan metode penelitian kualitatif dengan teknik pengumpulan data dengan cara wawancara, dan dokumentasi dengan metode deskriptif kualitatif. Hasil dari penelitian ini yaitu pemberian upah yang tidak sesuai dengan sistem hak upah menurut hukum Islam dan UMR/UMP yang berlaku.